2011
DOI: 10.1007/s00360-011-0554-6
|View full text |Cite
|
Sign up to set email alerts
|

Time domains of the hypoxic ventilatory response in ectothermic vertebrates

Abstract: Over a decade has passed since Powell et al. (Respir Physiol 112:123–134, 1998) described and defined the time domains of the hypoxic ventilatory response (HVR) in adult mammals. These time domains, however, have yet to receive much attention in other vertebrate groups. The initial, acute HVR of fish, amphibians and reptiles serves to minimize the imbalance between oxygen supply and demand. If the hypoxia is sustained, a suite of secondary adjustments occur giving rise to a more long-term balance (acclimatizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 204 publications
(273 reference statements)
0
39
0
1
Order By: Relevance
“…Whilst changes in chemoreceptor morphology and proliferation may contribute to the enhanced ventilatory responses observed in fish following acclimation to hypoxia for 1 to 3 weeks (Kerstens et al, 1979;Burleson et al, 2002), as it does in ventilatory acclimatization to hypoxia in mammals (Bisgard, 2000;Powell et al, 1998;Porteus et al, 2011;Kumar and Prabhakar, 2012), it remains to be determined if the blunted ASR response is due directly to these chemoreceptor changes, or due to a putative increased hyperventilatory response resulting from the acclimation period that may have mitigated the need for ASR and effectively reduced the ASR threshold. Confirmation of this will require studies directed at determining the ventilatory response to acute hypoxia in zebrafish after a similar period of acclimation, especially since time-dependent changes in the ventilatory response to hypoxia appear to occur in fish (Porteus et al, 2011). One report has indicated that acclimation of zebrafish to hypoxia for 28 days reduced basal ventilation without a significant effect on the acute response .…”
Section: Asr As a Chemoreflexmentioning
confidence: 99%
“…Whilst changes in chemoreceptor morphology and proliferation may contribute to the enhanced ventilatory responses observed in fish following acclimation to hypoxia for 1 to 3 weeks (Kerstens et al, 1979;Burleson et al, 2002), as it does in ventilatory acclimatization to hypoxia in mammals (Bisgard, 2000;Powell et al, 1998;Porteus et al, 2011;Kumar and Prabhakar, 2012), it remains to be determined if the blunted ASR response is due directly to these chemoreceptor changes, or due to a putative increased hyperventilatory response resulting from the acclimation period that may have mitigated the need for ASR and effectively reduced the ASR threshold. Confirmation of this will require studies directed at determining the ventilatory response to acute hypoxia in zebrafish after a similar period of acclimation, especially since time-dependent changes in the ventilatory response to hypoxia appear to occur in fish (Porteus et al, 2011). One report has indicated that acclimation of zebrafish to hypoxia for 28 days reduced basal ventilation without a significant effect on the acute response .…”
Section: Asr As a Chemoreflexmentioning
confidence: 99%
“…Many freshwater aquatic vertebrates may be subjected to hypoxic stress at more frequent and variable schedules than marine or terrestrial species (Nikinmaa, 2002;Pelster, 2002;Farrell, 2007;Tattersall and Ultsch, 2008;Porteus et al, 2011;Richards, 2011;Sandblom and Axelsson, 2011). In addition to the immediate cardiorespiratory physiological responses, which have been well characterized, freshwater fish can develop acclimatory phenotypes in response to hypoxic conditions, presumably affording greater hypoxic resistance during that hypoxic episode and perhaps any subsequent hypoxia challenge (Pelster, 2002;Richards, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In water, fishes typically respond to environmental hypoxia initially by increasing activity and using avoidance behaviour (Chapman and Mckenzie, 2009). If this fails, an acute hypoxic ventilatory response occurs within seconds to minutes: hyperventilation of the gills increases oxygen uptake by increasing the frequency and/or amplitude of opercular movements Porteus et al, 2011). In the few other fishes capable of reversible ILCM development, the water-breathing goldfish (Carassius auratus) and crucian carp (C. carassius), large ILCMs increased the critical partial pressure of oxygen (P crit ), the level of dissolved oxygen (DO) at which oxygen uptake can no longer be maintained (Sollid et al, 2003;Fu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%